Bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) in treatment-naïve and treatment-experienced people with HIV: 12-month virologic effectiveness and safety outcomes in the BICSTaR Japan cohort - Yoshiyuki Yokomaku; Katsuji Teruya; Dai Watanabe; Tomoyuki Endo; Rumi Minami; Nao Taguchi; Tali Cassidy; Andrea Marongiu; David Thorpe; Takuma Shirasaka; Shinichi Oka (PLoS ONE, 2025)
BICSTaR (BICtegravir Single Tablet Regimen) is an ongoing, observational cohort study assessing the virologic effectiveness and safety of bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) in treatment-experienced (TE) and treatment-naïve (TN) people with HIV across 14 countries over 24 months. We present 12-month outcomes from participants in the BICSTaR Japan cohort. Retrospective and prospective data were pooled from people with HIV aged ≥20 years receiving B/F/TAF within routine clinical care in Japan. Outcomes included virologic effectiveness (primary endpoint; HIV-1 RNA <50 copies/mL), CD4 count, CD4/CD8 ratio, drug-related adverse events (DRAEs), persistence, and patient-reported outcomes (prospective TN cohort only). Overall, 200 participants were enrolled and included in the 12-month analysis population (150 retrospective, 50 prospective; 116 TN and 84 TE). Most participants were male at birth (99%); median age was 34 years in TN and 45 years in TE participants. At 12 months, virologic effectiveness was high: 92% (90/98) of TN and 95% (72/76) of TE participants had HIV-1 RNA <50 copies/mL (missing = excluded analysis). Median (quartile [Q]1, Q3) CD4 cell count increased by +202.0 (126.0, 311.0) cells/μL in TN (p<0.001) and +11.0 (−60.0, 87.0) cells/μL in TE (p = 0.380) participants. Through 12 months, DRAEs were reported by 13% (25/200) of all participants (16% [18/116] TN, 8% [7/84] TE); diarrhea, weight gain, and headache were the most common. Most DRAEs were mild in severity and no severe DRAEs were reported. One TN participant (<1%; 1/116) and two TE participants (2%; 2/84) discontinued B/F/TAF due to DRAEs (macrocytic anemia, vertigo, diarrhea, and headache). Treatment persistence at 12 months exceeded 98% in both TN and TE participants. In prospective TN participants, improvements in bothersome symptom count and quality-of-life measures were observed. B/F/TAF demonstrated high levels of virologic effectiveness and tolerability in people with HIV treated as part of routine clinical care in Japan.